Distinct patterns of cytokine and angiogenic factor modulation and markers of benefit for vandetanib and/or chemotherapy in patients with non-small-cell lung cancer. - Hanrahan, E; Lin, H; Kim, E; Yan, S; Du, D; McKee, K; Tran, H; Lee, J; Ryan, A; Langmuir, P; Johnson, B; Heymach, J (2010)
PURPOSE: There is an unmet need for biomarkers for identifying patients likely to benefit from anticancer treatments, selecting dose, and understanding mechanisms of resistance. Plasma vascular endothelial growth factor (VEGF) and soluble VEGF receptor 2 (sVEGFR-2) are known to be modulated by VEGF pathway inhibitors. It is unknown whether chemotherapy or VEGFR inhibitor/chemotherapy combinations induce changes in these or other cytokines and angiogenic factors (CAFs) and whether such changes could be markers of benefit. METHODS: Thirty-five plasma CAFs were analyzed using multiplexed bead arrays and enzyme-linked immunosorbent assays from 123 patients with non-small-cell lung cancer in a randomized phase II study who received vandetanib, a VEGFR and epidermal growth factor receptor inhibitor, monotherapy carboplatin and paclitaxel (CP), or the combination (VCP). Changes in CAFs at days 8, 22, and 43 from baseline were correlated with progression risk. RESULTS: VEGF increased and sVEGFR-2 decreased by day 43 in the vandetanib arm, whereas a distinct pattern was observed in the CP and VCP arms, with significant decreases in interleukin (IL) -12, IL-1 receptor antagonist, and matrix metalloproteinase 9 (MMP-9) and increased macrophage chemoattractant protein 1. In each treatment arm, changes in different markers were associated with progression risk. For example, increases in IL-8 with VCP, MMP-9 with CP, and VEGF with vandetanib monotherapy were associated with increased progression risk, and increase in intercellular adhesion molecule 1 with vandetanib was associated with decreased risk. CONCLUSION: Vandetanib and chemotherapy treatment led to distinct patterns of CAF changes; the combination resembled chemotherapy alone. Changes in specific CAFs correlated with clinical outcome, but markers differed for each treatment arm. CAF profiling may provide insights into the biologic effects of treatment and identify drug-specific markers of activity and clinical benefit.